1998
DOI: 10.1002/jlb.64.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants attenuate anthralin-induced skin inflammation in BALB/c mice: role of specific proinflammatory cytokines

Abstract: Anthralin is the most common therapeutic agent among a small number of pro-oxidant, 9-anthrones effective in the topical treatment of psoriasis. However, the usefulness of this drug is diminished by toxic side effects, including skin irritation and inflammation. The activities of anthralin are believed to be mediated by the generation of reactive oxygen intermediates and anthrone radicals produced in the skin. In this study, the dermal inflammatory response to anthralin was determined using a mouse ear swellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Accumulating evidence indicates that oxidative stress is associated with inflammation, and thiol anti-oxidants, especially glutathione, have often been thought of as possible anti-inflammatory mediator (26). Indeed, oxidative stress plays an important role in many inflammatory diseases, including ICD (2729). A molecular mechanism for this association was first provided in 1991, with the finding that H 2 O 2 activates the transcription factor NF-κB, which is involved in the production of many inflammatory cytokines, while thiol anti-oxidants inhibit its activation (30).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that oxidative stress is associated with inflammation, and thiol anti-oxidants, especially glutathione, have often been thought of as possible anti-inflammatory mediator (26). Indeed, oxidative stress plays an important role in many inflammatory diseases, including ICD (2729). A molecular mechanism for this association was first provided in 1991, with the finding that H 2 O 2 activates the transcription factor NF-κB, which is involved in the production of many inflammatory cytokines, while thiol anti-oxidants inhibit its activation (30).…”
Section: Discussionmentioning
confidence: 99%
“…Bernard and coworkers [21] compared gene expression profiles using a customized cDNA microarray system in keratinocytes, reconstituted epidermis, and human skin and investigated the effect of retinoid treatments on gene expression. Other studies have looked at smaller numbers of specific gene responses to a variety of treatments in keratinocytes [22][23][24], cultured skin [20,25], mouse skin [26], and human skin [27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to directly damaging cellular components of the skin, oxygen radicals can act as chemical messengers [58,59] to influence signal transduction pathways or regulate gene expression of inflammatory cytokines via activation of transcription factors [60][61][62][63]. In support of this, recent studies with anthralin have shown that oxygen radicals generated from anthralin are responsible for the induction of proinflammatory cytokines such as IL-6, IL-8, and TNF-α, resulting in the recruitment of inflammatory cells [64,65]. Anthralin was also described as a novel inducer of the transcription factor NF-κB [66].…”
Section: Chemistry and Proposed Mechanism Of Actionmentioning
confidence: 93%